2007
DOI: 10.1007/s11104-007-9458-3
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity of diazotrophic bacteria within the soil, root and stem of field-grown maize

Abstract: Recent studies suggest a high diversity of diazotrophic bacteria in maize. However, none of these works have been based on a sufficient number of samples to provide reasonable quantitative estimates of diazotrophic bacterial diversity. Here we present the use of molecular tools and statistical inference to assess diazotrophic bacterial diversity within rhizosphere soils, roots and stems of field grown maize. DNA was isolated from the latter collected from six maize growing regions within the southern most stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
73
0
6

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(85 citation statements)
references
References 61 publications
6
73
0
6
Order By: Relevance
“…Thus, extraneous variation is minimized in this experiment relative to many studies that focus on the functional significance of soil communities. In addition, the diversity of the diazotrophic community in soil is typically far lower than that of the overall community, with estimates of nifH richness generally between 11-99 OTU 0.03 g À1 soil (Bothe et al, 2002;Izquierdo and Nusslein, 2006;Roesch et al, 2008). Regardless, the response of the diazotrophic community to the effects of tillage and biomass management that we observed was complex and differed with respect to the richness, evenness and the composition of the community.…”
Section: Discussionmentioning
confidence: 69%
“…Thus, extraneous variation is minimized in this experiment relative to many studies that focus on the functional significance of soil communities. In addition, the diversity of the diazotrophic community in soil is typically far lower than that of the overall community, with estimates of nifH richness generally between 11-99 OTU 0.03 g À1 soil (Bothe et al, 2002;Izquierdo and Nusslein, 2006;Roesch et al, 2008). Regardless, the response of the diazotrophic community to the effects of tillage and biomass management that we observed was complex and differed with respect to the richness, evenness and the composition of the community.…”
Section: Discussionmentioning
confidence: 69%
“…The rhizosphere harbors a multitude of microorganisms that are affected by both abiotic and biotic stresses. Among these are the dominant rhizobacteria that prefer living in close vicinity to the root or on its surface and play a crucial role in soil health and plant growth [16,17]. It has been noted by many workers that Pseudomonas, Bacillus, Arthrobacter, Azospirillum, Klebsiella, and Enterobacter, isolated from the rhizosphere of various crops, showed synergistic effects on plant growth [18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that different species are commonly found on multiple plant tissues and there are some with a preference for the leaves. 15,19,44 This shows that there is a correlation between endophytes and plant parts harbouring them. In the present study, Bt and non-Bt maize cultivars harboured unrelated genera that are commonly found as maize endophytes such as Pantoea, Bacillus, Enterobacter, Serratia, Yersinia, Stenotrophomonas, Pseudomonas and Acinetobacter (Table 1).…”
Section: Discussionmentioning
confidence: 88%
“…Few studies have delved into this important aspect of endophyte biology. 3,[17][18][19] In this study, we hypothesised that genetic modification of maize plants (such as Bt maize) might influence the diversity and functional attributes of endophytic bacteria associated with the plant. This led us to investigate the potential impacts of genetic modification of maize on the community composition and functions of cultivable bacterial endophytes from different plant parts that included leaves, stems, cobs and tassels/husks at two different plant growth stages.…”
Section: Introductionmentioning
confidence: 99%